Guest Editor's Introduction: Teacher Research on Classroom Discourse in Northern Canadian Communities - Judith C. Lapadat (Networks: An Online Journal for Teacher Research, 2000)
This special issue brings together a series of articles written by practitioners in a number of northern communities in British Columbia, all of whom are affiliated with UNBC's graduate program in Curriculum and Instruction. The region they are writing about is large, rugged, and sparsely populated. Prince George, centrally located and the site of the main UNBC campus, has a population of 75,000. There are seven other small cities in the 10,000-20,000 range, and the remainder of the population resides in small towns and villages.